2015
DOI: 10.1007/s10484-015-9317-6
|View full text |Cite
|
Sign up to set email alerts
|

Social Stressors at Work, Sleep, and Recovery

Abstract: Many employees in service work are required to work on Saturdays, recovering during work-free Sundays and working again Mondays. We examined the effects of social stressors at work on recovery status at Sunday noon and Monday noon, and investigated if sleep quality mediates the negative effects of social stressors at work on recovery. From Saturday until Monday morning, 41 participants wore actigraphs to measure sleep duration and sleep fragmentation. Social stressors at work were assessed by self-reported que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 33 publications
(43 reference statements)
2
21
0
Order By: Relevance
“…Again, previous studies were a bit controversial regarding age differences and workplace stressors. For example, Pereira et al found no significant links between age and social stressors [31]. Similarly, in a study by Kumar and Sundaram, the variables that included age groups were not found to be significantly associated with the stress level [44].…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Again, previous studies were a bit controversial regarding age differences and workplace stressors. For example, Pereira et al found no significant links between age and social stressors [31]. Similarly, in a study by Kumar and Sundaram, the variables that included age groups were not found to be significantly associated with the stress level [44].…”
Section: Discussionmentioning
confidence: 93%
“…For example, in a study by Spector and Zhou, gender was not significantly linked with perceived organizational support, role ambiguity or overload [42]. In the Pereira et al study, gender was not significantly linked to social stressors [31]. Li et al…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…It is important to understand the simultaneous effects of environmental stimuli and psychological profiles on the evolution of SD according to different age ranges, because stressors are the same and probably start to affect people at an early age. The allostatic load is a manifestation of this long exposure to stress, and people in the same community are affected differently even with the same stressors [58][59][60] .…”
Section: Relation Between Allostatic Load and Sleepmentioning
confidence: 99%